Foraminifera as tsunami tracers in Holocene sequences of Southwestern Spain - Guerra, Liliana (2013)
El objetivo de este trabajo es la identificación de eventos de alta energia (tsunamis?) em el P.N. de Doñana a partir del análisis de asociaciones de foraminíferos, llevando a cabo en un testigo corto, y comparar estos datos con el registro del Tsunami de 1755 que tuvo lugar en el SO de la Península Ibérica, donde los foraminíferos se han mostrado como indicadores muy útiles para caracterizar los paleoambientes pre- y postsunami y delimitar capas tsunamigénicas. The southwestern Spanish coast is a low-probability tsunamigenic area (e.g., Reichester, 2001), although sixteen tsunami have been documented for the time-period between 218 BC and 1900 AD (Campos, 1991). These high-energy events have tremendous morphological effects and drastic ecological impacts in coastal areas (Borrero, 2005) and cause the deposition of sedimentary beds with characteristic textural and mineralogical features (e.g. Babu et al., 2007).